Grace stirs it up - Casanova, Mary (Middleton, WI : American Girl Publishing, 2015)
Inspired by her grandparents' bakery and her recent visit to Paris, nine-year-old Grace leads her friends in starting La Petite Patisserie, making and selling French pastries at school and special events, but they soon discover that starting a new business is not always easy--or fun.
8+.
730
Accelerated Reader
Keywords: Entrepreneurship -- Juvenile fiction; Business enterprises -- Juvenile fiction; Friendship -- Juvenile fiction; Families -- Juvenile fiction; Bakeries -- Juvenile fiction; Bakers -- Juvenile fiction